Polishing cloth dresser

JP7633774B2Active Publication Date: 2025-02-20NIPPONALLOYCO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020123182
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-17
Publication Date
2025-02-20
Estimated Expiration
2040-07-17

AI Technical Summary

Benefits of technology

【0025】 本発明のドレッサーを用いることによって、研磨パッドの均一なパッド平坦性が確保されるため、パッド表面粗さRaを小さく維持し、低マイクロスクラッチを実現することができる。また、金属溶出も防止でき、製品歩留まりが向上する。特に、半導体製造のCMP研磨のパッドコンディショナーとして本発明のドレッサーを適用する場合、ウエハ基板の平坦性が向上して優れた品質が達成されるとともに、高い歩留まりも維持できる効果を奏でる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633774000006
    Figure 0007633774000006
  • Figure 0007633774000007
    Figure 0007633774000007
  • Figure 0007633774000001
    Figure 0007633774000001
Patent Text Reader

Abstract

To provide a dresser for polishing cloth that reduces micro-scratches and a metal elution amount dramatically more than before in a chemical mechanical planarization (CMP) process in semiconductor manufacturing.SOLUTION: A dresser for polishing cloth includes: a metal bonded layer formed at a surface of a metallic support material and to which multiple abrasive grains are bonded; and a coating layer for coating the metal bonded layer. The multiple abrasive grains have an average grain size d of 3 μm≤d<200 μm. The metal bonded layer is made of an Ni-based braze material. The coating layer is a chromium plated layer having a thickness of 1 μm or more and a crystalline structure.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing cloth dresser that is used in the chemical mechanical planarization (CMP) process to maintain the flatness of the polishing cloth and to remove clogging and foreign matter. [Background technology]

[0002] CMP polishing is used in equipment that polishes the surfaces of semiconductor wafers, or that flattens the surfaces of wiring and insulating layers during the manufacturing process of integrated circuits, and in equipment that flattens the surfaces of aluminum and glass plates used for magnetic hard disk substrates.

[0003] The CMP polishing is a method of flattening the surface to be polished by supplying a slurry liquid containing fine abrasive grains to a rotating substrate to which a polishing pad made of urethane is attached, and pressing the surface to be polished against the substrate. Naturally, the polishing ability of the polishing pad decreases with time of use, but in order to suppress this decrease, the surface of the polishing pad is ground at regular intervals to maintain the flatness of the polishing pad and to constantly dress the pad so that a new surface is always produced. The part used for this dressing is called a dresser, and the dresser is obtained by bonding abrasive grains to a metal substrate by electrochemical deposition or brazing.

[0004] Recently, there is a demand for extremely narrow lines / spaces in integrated circuits with wiring rules of up to 3 nm. As wiring rules become narrower, there is a growing demand to eliminate microscratch damage on the polished surface in order to improve yields in the CMP process. In addition, a problem has arisen regarding the prevention of metal elution from dressers, which was not previously required. This is because in advanced semiconductors with extremely narrow wiring rules, deterioration of electrical insulation due to metal elution can easily cause a drop in yield. In order to meet these demands, a dresser that can prevent metal elution while preventing the occurrence of microscratches is required.

[0005] Patent Document 1 discloses a dresser that can impart acid resistance to an abrasive layer to prevent the abrasive layer from being eroded when a strongly acidic abrasive is used, and that has a coating layer made of diamond-like carbon or molybdenum disulfide formed on the surface of an abrasive layer that is made up of abrasive grains and a nickel-plated layer to which the abrasive grains are fixed.

[0006] Patent Document 2 discloses a dresser that is free from diamond grains falling off and contamination due to dissolution of the binder and base metal, in which a bonding layer is formed by a single layer of diamond grains fixed to the surface of a metal base metal, and the bonding layer is coated with a ceramic coating. The material of the ceramic coating is selected from CrN, TiN, SiC, TiAlN, Si3N4, Al2O3, and DLC (Diamond Like Carbon).

[0007] Patent Document 3 discloses a dresser having enhanced corrosion resistance and abrasion resistance to reduce corrosion caused by slurry, the dresser having an abrasive layer on one side of a base metal made of stainless steel, in which abrasive grains are fixed in a metallic bonding phase, a base plating layer made of Au plating on the surface of the abrasive layer, and a hard corrosion-resistant plating layer made of Rh formed thereon.

[0008] Patent Document 4 discloses a dresser having excellent corrosion resistance against the acidic liquid in a slurry, which has abrasive grains fixed by a metal layer, and the fixing layer is covered with a synthetic resin layer containing a fluororesin having a cyclic perfluoroether structure.

[0009] Patent Document 5 discloses a dresser that can improve the adhesion of abrasive grains, prevent the aggregation of slurry, and prevent the elution of metal, in which abrasive grains are fixed by electrodeposition with a nickel plating layer and a water-repellent coating is formed on the upper surface of the nickel plating layer. This water-repellent coating is a composite plating layer made of nickel and a water-repellent resin.

[0010] Patent Document 6 discloses a dresser having improved corrosion resistance, wear resistance, and abrasive grain retention, in which the dresser has abrasive grains held by a nickel plating layer, and the nickel plating layer is covered with an amorphous chrome plating layer. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2000-127046 A [Patent Document 2] JP 2001-210613 A [Patent Document 3] JP 2003-117822 A [Patent Document 4] JP 2004-25377 A [Patent Document 5] JP 2008-229775 A [Patent Document 6] JP 2013-123771 A Summary of the Invention [Problem to be solved by the invention]

[0012] As mentioned above, dressers that prevent metal elution from dressers have been disclosed in the past. However, in Patent Documents 1, 2, 4, and 5, ceramic film or resin film is used as the coating film, so the adhesion between the coating film and the metal adhesion layer is insufficient, and polishing slurry may penetrate into the gap between the coating film and the metal adhesion layer, causing metal elution. In addition, the film quality of the coating film is not dense enough, so polishing slurry may penetrate into the metal adhesion layer through cracks present in the coating film, causing metal elution. In Patent Document 3, the problem is that rhodium plating is expensive.

[0013] In Patent Document 6, an amorphous chrome plating coating layer is used. Here, the amorphous chrome plating layer is very fragile, and the difference in thermal expansion coefficient between the base metal adhesion layer and the amorphous chrome plating layer and the stress applied during use as a dresser cause the amorphous chrome plating layer to crack, which leads to peeling of the film. Although the amorphous chrome plating layer itself has a metal elution prevention effect, the base metal adhesion layer comes into contact with the polishing slurry due to cracking or peeling, so the metal elution prevention effect as a dresser cannot be expected.

[0014] Furthermore, none of the above-mentioned Patent Documents 1 to 6 discloses any technology for preventing the occurrence of micro-scratches, and are therefore inadequate as dressers that can be used in the manufacturing processes of advanced semiconductors.

[0015] As mentioned above, the conventional technology is insufficient in preventing metal elution and does not take measures against micro-scratches, resulting in a dresser that significantly reduces yield. Due to the demand for further improvement in yield in the CMP process, a dresser that can prevent metal elution while preventing micro-scratches has been required.

[0016] SUMMARY OF THE PRESENT EMBODIMENT In order to solve the above-mentioned problems, an object of the present invention is to provide a dresser which prevents micro-scratches and further suppresses metal elution. [Means for solving the problem]

[0017] The gist of the present invention is as follows. (1) A dresser for an abrasive cloth comprising a metal adhesion layer formed on the surface of a metal support and having a plurality of abrasive grains adhered thereto, and a coating layer covering the metal adhesion layer, wherein the average particle size d of the plurality of abrasive grains is 3 μm≦d<200 μm, the metal adhesion layer is made of a Ni-based brazing material, and the coating layer is a crystalline chrome plating layer having a thickness of 1 μm or more. (2) The dresser for an abrasive cloth according to (1), further comprising a cover layer that covers the chrome plating layer.

[0018] (3) The dresser for a polishing cloth according to the above (1) or (2), wherein the crystal grain size of the chromium plating layer is 20 μm or less.

[0019] (4) The dresser for a polishing cloth according to any one of (1) to (3) above, wherein the crystal grain size of the chromium plating layer is 2 μm or less.

[0020] (5) A dresser for a polishing cloth according to any one of the preceding paragraphs (1) to (4), characterized in that the chrome plating layer has a thickness of 3 μm or more.

[0021] (6) A dresser for a polishing cloth according to any one of the preceding items (1) to (5), wherein the chrome plating layer has a thickness of 5 μm or more.

[0022] (7) A dresser for a polishing cloth according to any one of the above (1) to (6), characterized in that the average particle diameter d of the abrasive grains is 3 μm≦d<100 μm.

[0023] (8) The dresser for a polishing cloth according to any one of the preceding paragraphs (1) to (7), wherein the abrasive grains are at least one of diamond, cubic boron nitride, boron carbide, silicon carbide, and aluminum oxide.

[0024] (9) The dresser for a polishing cloth according to any one of the above (1) to (8), wherein the metallic support is made of stainless steel. Effect of the Invention

[0025] By using the dresser of the present invention, uniform pad flatness of the polishing pad is ensured, so that the pad surface roughness Ra can be kept small and low micro-scratches can be realized. In addition, metal elution can be prevented, and product yield can be improved. In particular, when the dresser of the present invention is applied as a pad conditioner for CMP polishing in semiconductor manufacturing, the flatness of the wafer substrate is improved, excellent quality is achieved, and a high yield can be maintained. [Brief description of the drawings]

[0026] [Figure 1] 1 shows a schematic cross-sectional view of a dresser of the present invention. [Diagram 2] 1 shows a schematic plan perspective view of a dresser of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] As mentioned above, in the CMP polishing process of advanced semiconductors with wiring rules of less than 10 nm, suppression of micro-scratches and a small amount of metal elution are important due to the demand for improved yield. In order to solve this problem, the present inventors have conducted extensive research and have invented the dresser shown in Figures 1 and 2. Figure 1 shows a schematic cross-sectional view of the dresser of the present invention. Figure 2 shows a schematic plan view perspective view of the dresser of the present invention. With reference to Figures 1 and 2, the dresser 100 of the present invention includes a metal adhesion layer 2 formed on a metal support 1 to which a plurality of abrasive grains 4 are adhered, and a coating layer 3 that covers the metal adhesion layer 2.

[0028] The inventor has found that micro-scratches can be suppressed when the pad surface roughness of the polishing pad is small. In order to reduce the pad surface roughness of the polishing pad, it is effective to make the particle size of the abrasive grains used in the dresser as small as possible. However, as the particle size is reduced, the bonding strength of the abrasive grains to the metal adhesion layer decreases, causing the abrasive grains to fall off during dressing, causing macrocracks on the polished surface, and significantly reducing the yield. Therefore, the inventor has used a brazing method with high bonding strength as a method for bonding the abrasive grains 4. A means for suppressing micro-scratches had not been found in the past, and this invention was discovered by the inventor through many experiments.

[0029] In order to suppress metal elution, a crystalline chromium plating film having high stability in an acidic solution was used as the coating layer 3. It was also found that by coating the metal fixing layer 2 using a Ni-based brazing material with a crystalline chromium plating layer, better adhesion can be obtained and metal elution can be suppressed compared with the case of applying a similar coating to a metal fixing layer using other brazing materials (e.g., Ag-based, Cu-based, Ti-based, etc.). The Ni-based brazing material is an alloy mainly composed of nickel and having a liquidus temperature higher than 450°C, and examples thereof include Ni-Cr-Fe-Si-B-based, Ni-Cr-Si-based, Ni-Cr-P-based, and Ni-Cr-Si-B-based materials represented by JIS standard materials such as BNi-1, BNi-1A, BNi-2, BNi-5, and BNi-7, but is not limited thereto. From the viewpoint of composition, the Ni-based brazing material may be, for example, a Ni-based brazing material that satisfies the composition conditions of Ni+Fe 70% by mass or more and 90% by mass or less (however, Fe / (Ni+Fe) is 0% by mass or more and 0.4% by mass or less), Cr 1% by mass or more and 25% by mass or less, and Si+B 2% by mass or more and 15% by mass or less (however, B / (Si+B) is 0% by mass or more and 0.8% by mass or less), but is not limited thereto. The present inventor has invented a dresser that can keep the pad surface roughness Ra small, suppress micro-scratches, and prevent metal elution by covering a metal fixing layer 2 made of a Ni-based brazing material to which small-diameter abrasive grains 4 are fixed with a crystalline chrome plating layer 3. Aiming to improve the yield of the CMP process, the pad surface roughness Ra, the number of micro-scratches, and the amount of metal elution were evaluated using various dressers with different grain sizes of abrasive grains and thicknesses of the crystalline chrome plating layer.

[0030] Specifically, CMP polishing was performed using various dressers with different grain sizes, and the pad surface roughness Ra and the number of microscratches were evaluated to determine the appropriate grain size of the abrasive. In addition, various dressers with different thicknesses of the crystalline chrome plating layer were dipped into the polishing slurry, and the amount of metal in the polishing slurry after dipping was analyzed to determine the appropriate thickness of the chrome plating layer. The results of this experiment and evaluation will be shown in detail in the Examples.

[0031] The present inventors have found that by controlling the grain size of the chromium crystals contained in the crystalline chromium plating layer to a small size, it is possible to further suppress the formation of penetrating cracks that reach the metal fixing layer beneath the crystalline chromium plating layer, and thus to further suppress the elution of metal. This point will also be described in detail in the Examples.

[0032] The dresser 100 may further include a cover layer that covers the coating layer 3 (crystalline chromium plating layer). Examples of the cover layer include, but are not limited to, a chromium plating layer having a composition similar to that of the coating layer 3 (crystalline chromium plating layer), a chromium plating layer having a composition different from that of the coating layer 3 (crystalline chromium plating layer), and a chromium carbide plating layer formed from chromium carbide. The cover layer may be a single layer or multiple layers.

[0033] <Reasons for Limiting the Invention> When the average particle size of the abrasive grains 4 is d, the average particle size d is 3 μm≦d<200 μm. If the abrasive grains are less than 3 μm, the pad grinding rate decreases and the polishing pad's dressing performance is insufficient, making it impossible to use it as a dresser. If the abrasive grains are 200 μm or more, the pad surface roughness Ra becomes large and it is not possible to prevent micro-scratches. If the average particle size d of the abrasive grains 4 is 3 μm≦d<100 μm, the pad surface roughness Ra becomes smaller and micro-scratches are more effectively suppressed.

[0034] The abrasive grain size can be measured by any method. For example, the abrasive grain size may be measured after peeling off and collecting the abrasive grains 4 before they are fixed, or after the fixed abrasive grains 4 are removed. In this case, the abrasive grain size may be the number average grain size obtained by sieve classification, laser diffraction, centrifugal sedimentation, direct observation with an optical microscope or a scanning electron microscope (SEM), or the like. In the present invention, it is preferable to use the number average grain size obtained by the laser diffraction method or the direct observation with an optical microscope or a scanning electron microscope. When the grain size of the fixed abrasive grains 4 is measured as it is, the number average grain size may be the number average grain size obtained from the circle equivalent diameter obtained by the direct observation with an optical microscope or a SEM.

[0035] The thickness of the crystalline chrome plating layer 3 is 1 μm or more. If it is less than 1 μm, the metal elution prevention effect is insufficient, but if it is 1 μm or more, the metal elution prevention effect is effective. If the thickness of the crystalline chrome plating layer 3 is 3 μm or more, the metal elution prevention effect is further improved, which is preferable. In particular, if the thickness of the crystalline chrome plating layer is 5 μm or more, the metal elution prevention effect is further improved, which is even more preferable.

[0036] The crystalline chrome plating layer 3 is generally a polycrystal (a chrome plating layer with a crystalline structure) consisting of fine crystals with a grain size of several tens of μm to submicrons. A known method can be used to measure the grain size of the crystalline chrome plating layer 3. The grain size can be a number average grain size obtained by a known method. The smaller the grain size of the crystalline chrome plating layer, the better the sealing performance against the polishing slurry and the better the metal elution prevention effect. The grain size is preferably 20 μm or less, and more preferably 2 μm or less since it can exert a greater metal elution prevention effect.

[0037] The abrasive grains 4 constituting the dresser for polishing cloth of the present invention are preferably those having high hardness and not easily reacting with acidic or alkaline slurries, and for example, abrasive grains 4 made of diamond, cubic boron nitride, boron carbide, silicon carbide, aluminum oxide, silicon oxide, or cerium oxide are used. Particularly preferred are abrasive grains 4 made of diamond, cubic boron nitride, boron carbide, silicon carbide, or aluminum oxide. One type of abrasive grains 4 may be used alone, or multiple types of abrasive grains 4 may be used in combination. It is also possible to use abrasive grains whose surfaces are coated with at least one selected from titanium, zirconium, and chromium, or at least one selected from titanium carbide, zirconium carbide, and chromium carbide.

[0038] In this way, the dresser of the present invention is a dresser that can prevent micro-scratches by controlling the particle size of the abrasive grains 4 of the dresser, and further suppresses the amount of metal elution by coating the metal fixing layer 2 using a Ni-based brazing material with a crystalline chrome plating layer 3. The present invention is an invention that has been realized by achieving both micro-scratches and metal elution suppression at the same time.

[0039] <Manufacturing method of the dresser according to the present invention> The dresser according to the present invention is manufactured as follows. The metal support 1 is preferably made of stainless steel, which is unlikely to react with acidic or alkaline slurries, like the abrasive grains 4. Typical stainless steels such as SUS304, SUS316, and SUS430 are suitable. General structural steels such as carbon steels with Ni or other plating on the surface can also be used.

[0040] Furthermore, the shape of the metal support material 1 is not particularly limited and may be a polygonal shape such as an octagon or an icosagon. However, since the metal support material 1 itself rotates while grinding the pad, it is preferable that it be disk-shaped in order to ensure uniform grinding properties.

[0041] Next, a Ni-based brazing material is applied to the surface of the metal support 1, and the abrasive grains 4 are arranged in a single layer at a predetermined interval on the applied Ni-based brazing material. Here, the single layer means that the abrasive grains 4 are arranged in a plane including the surface of the metal support 1. In this case, the abrasive grains 4 are temporarily fixed with glue or the like to prevent them from shifting.

[0042] Next, 10 -3 After drawing a vacuum to about Pa, a brazing heat treatment is performed by raising the temperature to a temperature at which the brazing material melts, and a metal fixing layer 2 is formed on the metal support 1. Note that the temperature at which a conventional brazing material is melted is preferably equal to or higher than the melting point of the brazing material, and is preferably as low as possible, and is preferably within a range of about the liquidus temperature + 20°C at most.

[0043] Crystalline chrome plating layers are formed as follows. A plating bath containing chromic anhydride (chromium trioxide) as the main component and sulfuric acid added as a catalyst at a weight ratio of about 1 / 100 of the chromic anhydride is used, with a bath temperature of 48 to 58°C and a current density of 15 to 35 amperes / dm 2 However, the method is not limited to the above. EXAMPLES

[0044] The present invention will be described in detail below with reference to examples. Example 1 Diamond abrasive grains having an average grain size d of 2 μm, 4 μm, 10 μm, 20 μm, 35 μm, 50 μm, 65 μm, 75 μm, 95 μm, 110 μm, 150 μm, 190 μm, 250 μm, and 300 μm were fixed to a metal adhesion layer formed on a metal support material made of SUS304 stainless steel, and the metal adhesion layer was coated with a crystalline chrome plating having a thickness shown in Table 1. The dressers shown in FIG. 1 and FIG. 2 were manufactured. Using these dressers, the pad surface roughness Ra, the number of micro scratches, and the amount of metal elution were evaluated. The crystal grain size of the crystalline chrome plating layer in each example and comparative example was 6 μm. There are various methods for measuring the crystal grain size, but in this example, the grain size was measured by observation on a two-dimensional plane using a microscope. The metal support material 1 was formed in a disk shape with a diameter of 108 mm and a thickness of 6 mm. The surface shape of the metal adhesion layer was formed in a flat shape. The metal adhesion layer was made of Ni-Cr-Si-B brazing filler metal, BNi-2 manufactured by Tokyo Blaze Co., Ltd.

[0045] <Evaluation of pad surface roughness Ra and number of micro-scratches> The fabricated dresser was applied to the CMP process of a patterned wafer, and the pad surface roughness Ra after the CMP process and the microscratch level of the patterned wafer were evaluated. The pad surface roughness Ra was measured using a laser surface roughness measuring instrument, and the microscratch level was measured using a defect inspection device manufactured by KLA-Tencor Corporation.

[0046] Regarding the pad surface roughness Ra (μm / min), if the pad surface roughness Ra was 4.9 (μm / min) or less, it was evaluated as "surface roughness is sufficiently small" and as "○", if it was more than 4.9 (μm / min), it was evaluated as "surface roughness is large" and as "×". In addition, if the pad surface roughness Ra was 2.9 (μm / min) or less, it was evaluated as "surface roughness is even more sufficiently small" and as "◎◎", if it was 2.4 (μm / min) or less, it was evaluated as "surface roughness is even more sufficiently small".

[0047] The microscratch level was set to 10 for the number of microscratches of No. 14, which had the largest average grain size of abrasive grains. The microscratch levels of No. 1 to No. 13 were calculated by dividing the number of microscratches of each by the number of microscratches of No. 14, multiplying the result by 10, and rounding off the first decimal place. As a result, when the microscratch level was 8 or less, it was evaluated as ○, meaning that the number of microscratches was sufficiently small, and when the microscratch level was 9 or more, it was evaluated as ×, meaning that the number of microscratches was large. In addition, when the microscratch level was 3 or less, it was evaluated as ◎, meaning that the number of microscratches was even smaller, and when the microscratch level was 2 or less, it was evaluated as ◎◎, meaning that the number of microscratches was even smaller.

[0048] <Evaluation of metal elution amount> The amount of metal elution from the dresser was evaluated by dipping the manufactured dresser in the polishing slurry for 72 hours, and the slurry after dipping was subjected to ICP analysis to evaluate the amount of metal elution (ppm). At this time, in order to grasp the amount of metal contained in the slurry from the beginning, the slurry before the dip test was also subjected to ICP analysis. The amount of metal elution from the dresser was determined by subtracting the amount of metal in the slurry before dipping from the amount of metal in the slurry after dipping. The elements analyzed by ICP were nickel, chromium, iron, copper, manganese, sodium, aluminum, cobalt, potassium, and magnesium, and the sum of the amounts of these metals was determined as the amount of metal elution from the dresser. As a result, when the amount of metal elution was 100 ppm or less, it was evaluated as ○, which means that "metal elution is sufficiently suppressed," and when the amount of metal elution was more than 100 ppm, it was evaluated as ×, which means that "metal elution is not sufficiently suppressed." In addition, when the amount of metal elution was 40 ppm or less, it was rated as ◎, meaning that "metal elution was more sufficiently suppressed," when the amount of metal elution was 15 ppm or less, it was rated as ◎◎, meaning that "metal elution was even more sufficiently suppressed," and when the amount of metal elution was 3 ppm or less, it was rated as ◎◎◎, meaning that "almost no metal elution occurred."

[0049] [Table 1]

[0050] As is clear from the comparison between the comparative examples and the examples in Table 1, in the examples of the present invention (samples No. 2 to 12), the evaluations of the pad surface roughness Ra, the microscratch level, and the amount of metal elution were all "○" or higher. On the other hand, in sample No. 1 (comparative example), since the average abrasive grain size is small at 2 μm, the pad surface roughness Ra is small, but the pad's sharpening performance is insufficient, and the evaluation of the microscratch level is "×". In addition, in samples No. 13 and No. 14 (comparative examples), since the abrasive grain size is too large, the pad surface roughness Ra becomes large, the microscratch increases, and the evaluation of the microscratch level is "×". In addition, when the average abrasive grain size d is 3 μm≦d<100 μm (samples No. 2 to 9), the pad surface roughness Ra becomes smaller (evaluation "◎" or higher). There has not been a dresser with less microscratch and less metal elution as in the examples.

[0051] Example 2 Diamond abrasive grains 4 with an average grain size d of 50 μm were fixed to a metal adhesion layer formed on a metal support material made of SUS304 stainless steel, and the metal adhesion layer was coated with crystalline chrome plating having the thickness shown in Table 2. The dresser shown in FIG. 1 and FIG. 2 was manufactured, and the amount of metal eluted from the dresser was evaluated. The crystal grain size of the crystalline chrome plating layer in each example and comparative example was 6 μm. The method of measuring the crystal grain size was the same as in Example 1. The metal support material 1 used was formed into a disk shape with a diameter of 108 mm and a thickness of 6 mm. The surface shape of the metal adhesion layer was formed into a flat shape. Ni-Cr-Fe-Si-B-based brazing material was used for the metal adhesion layer. BNi-1 manufactured by Tokyo Blaze Co., Ltd. was used as the Ni-Cr-Fe-Si-B-based brazing material.

[0052] <Evaluation of metal elution amount> The amount of metal eluted from the dresser was evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0053] [Table 2]

[0054] As can be seen from the examples in Table 2, by making the crystalline chrome plating thickness 1 μm or more (samples No. 23 to No. 29), it became possible to suppress metal elution. Furthermore, the effect of suppressing metal elution was remarkable when the chrome plating thickness was 3 μm or more (sample No. 25), and in particular, the effect of suppressing metal elution was more desirable when the chrome plating thickness was 5 μm or more (samples No. 26 to No. 29). On the other hand, when the crystalline chrome plating thickness was less than 1 μm, metal elution was not sufficiently suppressed, and the evaluation was "x".

[0055] Example 3 Diamond abrasive grains 4 with an average grain size d of 50 μm were fixed to a metal adhesion layer formed on a metal support material made of SUS304 stainless steel, and a crystalline chrome plating layer with a thickness of 9 μm was coated on the metal adhesion layer, with the grain size changed as shown in Table 3. The dresser shown in FIG. 1 and FIG. 2 was manufactured, and the amount of metal elution from the dresser was evaluated. In addition, the adhesion of the crystalline chrome plating film to the metal adhesion layer was also evaluated. The grain size of the crystalline chrome plating layer was measured with a microscope as in Example 1. The metal support material 1 used was formed into a disk shape with a diameter of 108 mm and a thickness of 6 mm. The surface shape of the metal adhesion layer was formed into a flat shape. Ni-Cr-Si-B-based brazing material was used for the metal adhesion layer. BNi-2 manufactured by Tokyo Blaze Co., Ltd. was used as the Ni-Cr-Si-B-based brazing material. In this example, as comparative examples, the case where an amorphous chrome plating film was coated and the case where a Cu-Ag-P-based brazing material was used for the brazing material were also evaluated. As the Cu-Ag-P based brazing material, BCuP-3 manufactured by Tokyo Blaze Co., Ltd. was used.

[0056] <Evaluation of the amount of metal elution and the adhesion of chrome plating film to metal adhesion layer> The amount of metal eluted from the dresser was evaluated in the same manner as in Example 1. The adhesion of the chrome plating layer was evaluated by dressing the polishing pad continuously for 20 hours and the condition of the chrome plating layer on the dresser surface after dressing was evaluated under a microscope. If no cracks or peeling were observed and the condition was the same as before dressing, it was evaluated as ○, and if cracks or peeling were observed, it was evaluated as ×. The results are shown in Table 3.

[0057] [Table 3]

[0058] As can be seen from the examples in Table 3, by forming a crystalline chrome plating layer on a metal adhesion layer using Ni-Cr-Si-B brazing material (samples No. 32 to No. 39), metal elution was suppressed (evaluated as "◎" or better). Also, by making the crystal grain size of the chrome plating layer 20 μm or less (samples No. 33 to No. 37), the effect of suppressing metal elution was remarkable (evaluated as "◎◎"). Furthermore, by making the crystal grain size of the chrome plating layer 2 μm or less (samples No. 38 to No. 39), the effect of suppressing metal elution was even more remarkable (evaluated as "◎◎◎"). When the crystalline chrome plating layer was applied, no cracking or peeling was observed, and it was at a level that could be used as a dresser.

[0059] On the other hand, when the amorphous chrome plating layer of sample No. 31, which is a comparative example, was coated, the amorphous chrome plating layer was extremely brittle, and the difference in thermal expansion coefficient between the base metal adhesion layer and the amorphous chrome plating layer and the stress applied during use as a dresser caused the amorphous chrome plating layer to crack and peel off, resulting in adhesion of x. In addition, the amount of metal elution was 187 ppm (evaluated as x), and metal elution could not be suppressed.

[0060] In addition, when the Cu-Ag-P brazing filler metal of sample No. 40, which is a comparative example, was used, the adhesion between the crystalline chrome plating layer and the metal fixing layer made of the Cu-Ag-P brazing filler metal was insufficient, and in the adhesion evaluation, cracks and peeling occurred in the crystalline chrome plating layer, and the adhesion was evaluated as x. In addition, the amount of metal elution was 109 ppm (evaluated as x), and metal elution could not be suppressed.

[0061] Example 4 Diamond abrasive grains 4 with an average grain size d of 50 μm were fixed to a metal adhesion layer formed on a metal support material made of SUS304 stainless steel, and a crystalline chrome plating layer with a thickness of 9 μm was coated on the metal adhesion layer, with the grain size changed as shown in Table 4. The dresser shown in FIG. 1 and FIG. 2 was manufactured, and the amount of metal elution from the dresser was evaluated. In addition, the adhesion of the crystalline chrome plating film to the metal adhesion layer was also evaluated. The grain size of the crystalline chrome plating layer was measured with a microscope as in Example 1. The metal support material 1 used was formed into a disk shape with a diameter of 108 mm and a thickness of 6 mm. The surface shape of the metal adhesion layer was formed into a flat shape. Ni-Cr-Fe-Si-B brazing material was used for the metal adhesion layer. BNi-1 manufactured by Tokyo Blaze Co., Ltd. was used as the Ni-Cr-Fe-Si-B brazing material. In this example, the case where an amorphous chrome plating film was coated was also evaluated as a comparative example.

[0062] <Evaluation of the amount of metal elution and the adhesion of chrome plating film to metal adhesion layer> The amount of metal eluted from the dresser and the adhesion of the chrome plating layer were evaluated in the same manner as in Example 3. The results are shown in Table 4.

[0063] [Table 4]

[0064] As can be seen from the examples in Table 4, by forming a crystalline chrome plating layer on a metal fixing layer using Ni-Cr-Fe-Si-B brazing material (samples No. 42 to No. 49), metal elution was suppressed (evaluated as "◎" or better). Also, by making the crystal grain size of the chrome plating layer 20 μm or less (samples No. 43 to No. 47), the effect of suppressing metal elution was remarkable (evaluated as "◎◎"). Furthermore, by making the crystal grain size of the chrome plating layer 2 μm or less (samples No. 48 to No. 49), the effect of suppressing metal elution was even more remarkable (evaluated as "◎◎◎"). When the crystalline chrome plating layer was applied, no cracking or peeling was observed, and it was at a level that could be used as a dresser.

[0065] On the other hand, when the amorphous chrome plating layer of sample No. 41, which is a comparative example, was coated, the amorphous chrome plating layer cracked and peeled off due to the difference in thermal expansion coefficient between the base metal adhesion layer and the amorphous chrome plating layer and the stress applied during use as a dresser, similar to the amorphous chrome plating layer of Example 3, and the adhesion was evaluated as x. In addition, the amount of metal elution was 181 ppm (evaluated as x), and metal elution could not be suppressed.

[0066] Example 5 Diamond abrasive grains 4 with an average grain size d of 50 μm were fixed to a metal adhesion layer formed on a metal support material made of SUS304 stainless steel, and a crystalline chrome plating layer with a thickness of 9 μm was coated on the metal adhesion layer, with the grain size changed as shown in Table 5. The dresser shown in FIG. 1 and FIG. 2 was manufactured, and the amount of metal elution from the dresser was evaluated. In addition, the adhesion of the crystalline chrome plating film to the metal adhesion layer was also evaluated. The grain size of the crystalline chrome plating layer was measured with a microscope as in Example 1. The metal support material 1 used was formed into a disk shape with a diameter of 108 mm and a thickness of 6 mm. The surface shape of the metal adhesion layer was formed into a flat shape. Ni-Cr-Si-based brazing material was used for the metal adhesion layer. BNi-5 manufactured by Tokyo Blaze Co., Ltd. was used as the Ni-Cr-Si-based brazing material. In this example, the case where an amorphous chrome plating film was coated was also evaluated as a comparative example.

[0067] <Evaluation of the amount of metal elution and the adhesion of chrome plating film to metal adhesion layer> The amount of metal eluted from the dresser and the adhesion of the chrome plating layer were evaluated in the same manner as in Example 3. The results are shown in Table 5.

[0068] [Table 5]

[0069] As can be seen from the examples in Table 5, by forming a crystalline chrome plating layer on a metal adhesion layer using Ni-Cr-Si brazing material (samples No. 52 to No. 59), metal elution was suppressed (evaluated as "◎" or better). Also, by making the crystal grain size of the chrome plating layer 20 μm or less (samples No. 53 to No. 57), the effect of suppressing metal elution was remarkable (evaluated as "◎◎"). Furthermore, by making the crystal grain size of the chrome plating layer 2 μm or less (samples No. 58 to No. 59), the effect of suppressing metal elution was even more remarkable (evaluated as "◎◎◎"). When the crystalline chrome plating layer was applied, no cracking or peeling was observed, and it was at a level that could be used as a dresser.

[0070] On the other hand, when the amorphous chrome plating layer of sample No. 51, which is a comparative example, was coated, the amorphous chrome plating layer cracked and peeled off due to the difference in thermal expansion coefficient between the base metal adhesion layer and the amorphous chrome plating layer and the stress applied during use as a dresser, similar to the amorphous chrome plating layer of Example 3, and the adhesion was evaluated as x. In addition, the amount of metal elution was 186 ppm (evaluated as x), and metal elution could not be suppressed.

[0071] From the above, it was found that metal elution can be suppressed by covering the crystalline chrome plating layer with a metal fixing layer made of Ni-based brazing material. Furthermore, the effect of suppressing metal elution is remarkable when the crystal grain size of the chrome plating layer is 20 μm or less, and it has a more desirable effect of suppressing metal elution when the crystal grain size is 2 μm or less. [Explanation of symbols]

[0072] 1 Metal support 2 Metal fixed layer 3 Crystalline chrome plating layer 4. Abrasive grain 100 Dresser

Claims

1. A dresser for an abrasive cloth comprising: a metal adhesion layer formed on a surface of a metal support, the metal adhesion layer having a plurality of abrasive grains adhered thereto; and a coating layer that covers the metal adhesion layer, The average particle diameter d of the plurality of abrasive grains is 3 μm≦d<200 μm, The metal adhesion layer is made of a Ni-based brazing material, 13. A dresser for an abrasive cloth, comprising: a polishing cloth dresser, the polishing cloth dresser comprising: a polishing cloth dresser for dressing an abrasive cloth;

2. The polishing cloth dresser also has 2. The dresser for a polishing cloth according to claim 1, further comprising a cover layer that covers the chrome plating layer.

3. 3. The dresser for a polishing cloth according to claim 1, wherein the crystal grain size of the chromium plating layer is 20 [mu]m or less.

4. 4. The dresser for a polishing cloth according to claim 1, wherein the crystal grain size of the chromium plating layer is 2 [mu]m or less.

5. 5. The dresser for a polishing cloth according to claim 1, wherein the chromium plating layer has a thickness of 3 [mu]m or more.

6. 6. The dresser for a polishing cloth according to claim 1, wherein the chromium plating layer has a thickness of 5 [mu]m or more.

7. 7. The dresser for a polishing cloth according to claim 1, wherein the average particle diameter d of the abrasive grains is in the range of 3 [mu]m≦d<100 [mu]m.

8. 8. The dresser for a polishing cloth according to claim 1, wherein the abrasive grains are at least one of diamond, cubic boron nitride, boron carbide, silicon carbide, and aluminum oxide.

9. 9. A dresser for an abrasive cloth according to claim 1, wherein the metallic support is made of stainless steel.

Citation Information

Patent Citations

  • Substantially pore-less formed body comprising polycrystal alpha- and / or beta-silicon carbide and manufacture

    JP1983009880A

  • Method for reading data of electronic device

    JP1984057317A

  • Electrodeposition dresser for polishing by polisher

    JP2000127046A

  • Pad conditioner for cmp

    JP2001210613A

  • Cmp conditioner and method of manufacturing the conditioner

    JP2003117822A